A Faunistic Study of the Short-horned Grasshoppers (Orthoptera: Acridomorpha) in Ilam Province, Iran - Hojat Aref; Mohsen Mofidi-Neyestanak; Mahmoud Shodjai; Sohrab Imani (تاکسونومی و بیوسیستماتیک, 2021)
The insect fauna of Ilam province is largely unknown. The orthopterans (Insecta: Orthoptera) are usually herbivores and some of them are considered as pests of crops. During 2015-2017, short-horned grasshoppers of Ilam province were collected using standard insect sweeping nets. Species identity determinations were performed using the morphological features of the collected materials through valid identification keys and comparison with type specimens already deposited in the Hayk Mirzayans Insect Museum. Consequently, 35 species belonging to 23 genera, from 10 subfamilies and 3 families were listed, of which 34 species were new reports for Ilam province insect fauna: ACRIDIDAE: Acridinae: Acrida bicolor, A. oxycephala, Cyrtacanthacridinae: Anacridium aegyptium, Schistocerca gregaria, Calliptaminae: Calliptamus barbarus, C. coelesyriensis, C. italicus, C. turanicus, Dericorythinae: Dericorys albidula, Eyprepocnemidinae: Heteracris pterosticha, Gomphocerinae: Chorthippus brunneus, Dociostaurus hauensteini, D. maroccanus, Ochrilidia tibialis, Stenohippus xanthus, Oedipodinae: Acrotylus insubricus, Aiolopus thalassinus, Locusta migratoria, Mioscirtus wagneri, Oedipoda miniata, O. caerulescens, Oedaleus senegalensis, Pyrgodera armata, Sphingonotus caerulans, S. savignyi, S. satrapes, S. octofasciatus, S. rubescens, Truxalinae: Truxalis nasuta. PAMPHAGIDAE: Thrinchinae: Asiotmethis limbatus, A. tauricus, Eremopeza reducta, E. soltanii. PYRGOMORPHIDAE: Pyrgomorphinae: Chrotogonus trachypterus, Pyrgomorpha conica. The number of species and genera reported indicates the species richness in the studied area and thus the need for more research to investigate the fauna.